The Importance of Customs Harmonization Between Asean Countries to Enhance Regional Trade Flow - Dwi Tiara Kurnilasari (DE'RECHTSSTAAT, 2025)
This article explores the critical role of customs harmonization in advancing regional economic integration within the ASEAN framework. Despite significant progress in tariff liberalization, ASEAN continues to face operational and legal fragmentation in customs administration, which undermines intra-regional trade and supply chain efficiency. Through a normative comparative analysis with other regional blocs, such as the European Union, MERCOSUR, and SACU, this study identifies structural gaps, institutional asymmetries, and policy inconsistencies that hinder effective integration. It proposes a multi-dimensional strategy involving modernization, regulatory reform, cross-border cooperation, and legal alignment with international standards such as the Revised Kyoto Convention and WTO Trade Facilitation Agreement. The study emphasizes that harmonized customs procedures reduce transaction costs, improve clearance times, and foster mutual trust and institutional cohesion among member states. It concludes that achieving a fully integrated customs environment is fundamental for ASEAN to transition from a free trade area to a customs union and to ensure the long-term resilience of the ASEAN Economic Community.